2018
DOI: 10.1111/mcn.12694
|View full text |Cite
|
Sign up to set email alerts
|

“Then you raise them with Shirchoy or cookies”: Understanding influences on delayed dietary diversity among children in Tajikistan

Abstract: Dietary diversity is a key component of infant and young child feeding (IYCF) as well as adult health. In Tajikistan, a predominantly rural, former Soviet country in Central Asia, we conducted formative research to identify barriers to dietary diversity and strategies for nutrition behaviour change. In Spring, 2016, mixed-methods data collection took place across 13 villages in all five regions, collecting collaborative mapping; structured assessments of stores and markets; home visits for dietary recalls; foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
(11 reference statements)
3
4
3
2
Order By: Relevance
“…and 2016 DHS Timor-Leste data found that mothers' achievement of MDD was lower than for young children when using the seven-food group indicator (University Research Co., 2018). In contrast, in rural Tajikistan, MDD-W was largely achieved by mothers while less than half of children 6-23 months met MDD, despite child and maternal DDS were positively associated (Klassen et al, 2019), analogous to our findings. Research among U.K. dyads concluded that the quality of mothers' diets was the leading explanatory factor informing children's dietary quality (Fisk et al, 2011), highlighting that shared family patterns are also expressed in resource-abundant settings.…”
Section: Seasonal Variation Of Dietssupporting
confidence: 87%
“…and 2016 DHS Timor-Leste data found that mothers' achievement of MDD was lower than for young children when using the seven-food group indicator (University Research Co., 2018). In contrast, in rural Tajikistan, MDD-W was largely achieved by mothers while less than half of children 6-23 months met MDD, despite child and maternal DDS were positively associated (Klassen et al, 2019), analogous to our findings. Research among U.K. dyads concluded that the quality of mothers' diets was the leading explanatory factor informing children's dietary quality (Fisk et al, 2011), highlighting that shared family patterns are also expressed in resource-abundant settings.…”
Section: Seasonal Variation Of Dietssupporting
confidence: 87%
“…The national MDD score was adequate with 80.7% of women consuming at least five out of 10 food groups over 24 hr prior to the interview. This was comparable with another study conducted in spring 2016 in Tajikistan, showing similar values for women (87%) but reporting a serious problem in the diversity of children' diet, with only 42% of children aged 6–24 months meeting the WHO guidelines for MDD (Klassen et al, ). Unfortunately, children' dietary diversity data are missing in the current study.…”
Section: Discussionsupporting
confidence: 86%
“…Klassen et al, 2019). Unfortunately, children' dietary diversity data are missing in the current study.…”
mentioning
confidence: 91%
“…For vulnerable populations, increasing consumption of ‘nutrient-rich foods’ can be achieved through multiple strategies, including own-food production among the rural poor, better incomes, and enhanced market availability and access for all consumers. Nevertheless, we are also learning more about specific barriers to adoption of better diets, for example, the complexity of linkages between agroecological, economic and social systems and education, and cultural barriers including food taboos on maternal behaviour patterns and infant and young child feeding practices ( Klassen et al, 2019 , Chegere and Stage, 2020 ).…”
Section: Shifting Agri-nutrition Prioritiesmentioning
confidence: 99%